2015
DOI: 10.1007/s10517-015-3149-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Status and Predisposing Genes in Patients with Diabetes Mellitus Type 1 from Various Ethnic Groups

Abstract: The peculiarities of HLA class II profile and lipid metabolism were examined in Buryat and Russian ethnic groups of patients with diabetes mellitus type 1. The incidence of type 1 haplotypes in HLA class II gene family was lower in Buryats than that in Russians. In comparison with Russians, the course of diabetes mellitus type 1 in Buryat patients was characterized with a lower content of total lipids, triacylglycerols, total cholesterol, and LDL, which probably explains a more favorable course of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…Therefore, variations in the antioxidant enzymes activities in testes, which independently or synergistically occur with free radicals, might be contributed to the impaired spermatogenesis and male infertility. Supporting this finding, it has been found that GSH levels, the activities of GR and GPx, were decreased in infertile men compared with the control group . Moreover, N‐nitrosamines caused severe inflammations and consequently increased the levels of cytokines, tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1 α) and interleukin 1 beta (IL‐1 β) cytokines in the male reproductive tract (testis, epididymis and sperm) .…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, variations in the antioxidant enzymes activities in testes, which independently or synergistically occur with free radicals, might be contributed to the impaired spermatogenesis and male infertility. Supporting this finding, it has been found that GSH levels, the activities of GR and GPx, were decreased in infertile men compared with the control group . Moreover, N‐nitrosamines caused severe inflammations and consequently increased the levels of cytokines, tumor necrosis factor‐alpha (TNF‐α), interleukin‐1 alpha (IL‐1 α) and interleukin 1 beta (IL‐1 β) cytokines in the male reproductive tract (testis, epididymis and sperm) .…”
Section: Discussionmentioning
confidence: 84%
“…Так, было доказано, что степень интенсивности липопероксидных процессов у пациентов бу-рятского ýтноса с сахарным диабетом 1-го типа снижена по сравнению с русскими (более низкий уровень первичных и промежуточных продуктов, повышенные значения общей антиокислительной активности), что подтверждается и низкими зна-чениями коýффициента окислительного стресса [77]. Течение СД1 у бурят также характеризует-ся сниженными значениями общих липидов, три-ацилглицеридов, общего холестерина и липопро-теинов низкой плотности, что, вероятно, может способствовать более благоприятному течению заболевания у бурят [78]. По полученным ранее клиническим данным выявлено, что поздние со-судистые осложнения (диабетическая ретинопа-тия и диабетическая нефропатия) у больных СД1 бурятского ýтноса встречаются реже относитель-но среднестатистических показателей [79,80].…”
Section: обзоры и лекцииunclassified
“…Многочисленные исследования показали, что особенности липидного обмена обусловлены генетическими факторами, зависят от характера питания, физической активности, возраста, пола и т. д. [3,8,18]. Нами было зарегистрировано увеличение ТАГ у студентов-индийцев -как у юношей, так и у девушек.…”
Section: результаты и обсуждениеunclassified
“…Как структурные компоненты липиды могут составлять до 25 % объёма нервных тканей, поэтому их недостаток либо избыток может привести к серьёзному снижению эффективности умственной и физической деятельности [11,12,16,20]. Показано, что содержание липидов в составе плазмы крови полностью отражает обмен липидов в организме в целом и особенно в печени и жировых депо [3,14,17,18,19]. Интересным представляется установленный факт, что примерно двое из сотни обучающихся в вузе во всем мире -иностранные студенты, среди которых преобладают граждане развивающихся стран [5].…”
Section: Introductionunclassified